Decreased total cholesterol levels in rats administered with chitosan from Green mussel (Perna viridis L.) shells - Keni Idacahyati; Yunia Amalia; Tresna Lestari (Pharmaciana, 2020)
Chitosan has been known to have anti-cholesterol activity. This linear polysaccharide can be derived from the chitin of green mussel shells by deacetylation. The purpose of this research was to find out the effects of administering chitosan from green mussel (Perna viridis L.) shells on total cholesterol levels. Chitosan was prepared in three steps, namely deproteinization, demineralization, and deacetylation. FTIR was used for characterization, and the absorbance values were calculated to obtain the degree of deacetylation. A total of 24 male Wistar rats were fed with high-fat ingredients (yolk, quail, used cooking oil) and 1% PTU for 30 days p.o and divided into six (6) groups, namely the normal control group, negative control (PGA 1%), positive control (Simvastatin at 0.9 mg/Kg BW), Dose 1 (chitosan at 250 mg/Kg b.w), Dose 2 (chitosan at 500 mg/Kg BW), and Dose 3 (chitosan at 750mg/Kg BW). The chitosan of green mussel shells had a deacetylation degree of 43.05%. The results showed that the three doses of chitosan exhibited reduced total cholesterol levels in the test rats. At a dose of 750 mg/Kg BW, chitosan led to the most significant reduction of total cholesterol levels in rats from averagely 127.1 to 74.2 mg/dL.